A rare case of simultaneous pneumoperitoneum and pneumomediastinum without hollow viscus perforation - Agrawal, Milan; Juneja , Iliyas A. (International Surgery Journal, 2024)
Traumatic pneumoperitoneum and pneumomediastinum managed conservatively are rare in surgical practice. This report describes an atypical case of 10-year-old male child with pneumoperitoneum, pneumomediastinum, extensive subcutaneous emphysema and an exceptionally rare finding of air in spinal canal, all managed conservatively. We report a case of 10 years old male child who presented with a compressed air injury to the perianal region. On further investigation, a diagnosis of traumatic pneumoperitoneum, pneumomediastinum and subcutaneous emphysema without hollow viscus perforation was established. He was managed conservatively. This case highlights the successful conservative management of child with traumantic pneumoperitoneum and pneumomediastinum. Many times explorative laparotomy is performed based on findings of pneumoperitoneum on abdominal radiograph and computed tomography (CT), which later turns out to be negative. Hence, clinical judgements may override trauma protocols in selected cases. Pneumoperitoneum preceded by a reasonable clinical history in patient with adequate abdominal examination may warrant continued observation, thus avoiding an unnecessary laparotomy.